A simplified preparation method for single-nucleus RNA-sequencing using long-term frozen brain tumor tissues - Ernst, Kati; Okonechnikov, Konstantin; Bageritz, Josephine; Perera, Ashwyn Augustine; Mallm, Jan-Philipp; Wittmann, Andrea; Maaß, Kendra K.; Leible, Svenja; Boutros, Michael; Pfister, Stefan; Zuckermann, Marc; Jones, David T. W. (Scientific reports, 2025)
Single-cell RNA-sequencing has provided intriguing new insights into research areas such as developmental processes and tumor heterogeneity. Most approaches, however, rely on the availability of fresh surgical specimens, thereby dramatically reducing the ability to profile particularly rare tissue types. Here, we optimized a method to isolate intact nuclei from long-term frozen pediatric glioma tissues. We performed a technical comparison between different single-nucleus RNA-sequencing (snRNA-seq) systems and applied the established nucleus isolation method to analyze frozen primary glioma tissues. The results show that our fast, simple and low-cost nuclear isolation protocol provides intact nuclei, which can be used in both droplet- and plate-based single-cell sequencing platforms - allowing the identification of distinct tumor cell populations and infiltrating microglia. Additional optimization to include shorter RNA fragments in the 3’ sequencing library improved gene detection and cell type annotation. Taken together, the method dramatically increases the potential of studying rare tumor entities and is specifically tailored for using frozen brain tumor tissue.